Subcritical vibrations of a large flexible rotor efficiently reduced by modifying the bearing inner ring roundness profile. (15th September 2018) - Viitala, Raine; Widmaier, Thomas; Kuosmanen, Petri
Highlights: Bearing inner ring was deformed to investigate subcritical vibration. Low-order inner ring waviness (2nd, 3rd and 4th) was studied. Minimizing the roundness error substantially reduced the subcritical vibrations. Roundness of the bearing inner ring was measured while installed on the rotor shaft. Abstract: Undesired vibration of a rotor is harmful for industrial processes and decreases the machine lifetime. In industrial processes, large rotors are commonly operated below the critical speed. In the subcritical speed range, the bearings are an important excitation source of vibration. The bearing inner ring based excitation is observed at a frequency, which is the rotor rotating frequency multiplied by the number of undulations in the roundness profile of the roller race of the bearing inner ring. Subcritical resonance occurs, when the bearing excitation frequency equals the natural frequency of the rotor system. The present study investigates the effect of the bearing inner ring roundness profile on the subcritical vibrations of a flexible rotor. The roundness profile of the bearing inner ring was measured, while installed on the rotor shaft. The roundness profile was modified to five different geometries to investigate different excitation cases. Finally, the roundness error of the inner ring was minimized. The rotor subcritical vibration was measured with each bearing inner ring geometry in the horizontal and vertical directions. The analysis was focused on the 2nd, 3rd and 4th harmonic vibration components, occurring at 1/2, 1/3 and 1/4 of the critical rotational speed. The results clearly suggest that the roundness profile of the roller race of the bearing inner ring affects the rotor subcritical vibration significantly. The increased waviness components of the bearing inner ring roundness profile increased the corresponding subcritical vibration amplitude. Minimizing the roundness error decreased the subcritical vibration substantially.